TRANSFORMASI DIGITAL DALAM EKONOMI MODERN - Mukhlis Mukhlis; Arsad Arsad; Zainuddin Mukhsin; Sitaman Said (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This paper aims to analyze and describe theoretically the Digital Transformation in the Modern Economy.